The WorldatWork handbook of total rewards a comprehensive guide to compensation, benefits, HR & employee engagement - WorldatWork (Organization) (Wiley, 2021)
"The world of work is changing; Baby Boomers are leaving the workforce and Millennials will be the largest segment of the workforce by 2020. In addition, the Gig Economy has given birth to an entirely different definition of "workforce." Organizations no longer solely employ traditional "employees"; rather, the workforce of today and into the future is comprised of traditional employees that are both onsite and remote. The core tenets of rewards -- compensation, benefits, work-life -- remain fundamentally critical for the workforce at-large. Yet the shifting demographic of "worker" is requiring employers to strategically re-think their approach to attracting, retaining and motivating the workforce. Workforce engagement is becoming ever-more critical to effectively attracting and rewarding the modern-day workforce. Since publication, the first edition has been the definitive authority on compensation and rewards from the world's leading professional association in the area, WorldatWork. This completely revised second edition broadens the scope to address the latest issues facing employers today and in the next five years. The world of work and rewards has changed significantly in the time since the initial WorldatWork Handbook of Compensation, Benefits & Total Rewards was published. Human resources and total rewards professionals need tools to equip them to manage a changing workforce that is influenced by multiple factors, particularly the Gig Economy and a new generation of workers that requires a different value proposition. Audiences with interest in human resources and rewards need a resource for gaining a solid understanding of the nuances in their professions. Readers will gain an understanding of the basics of rewards and what's required for foundational rewards programs, along with a higher-level view of how these programs support the overall goals of attracting, retaining, motivating and engaging that talent required to deliver business success."--